Optimization of Natural Lighting Design for Visual Comfort in Modular Classrooms: Temuco Case. Issue 1 (May 2020) - Callejas, L; Pereira, L; Reyes, A; Torres, P; Piderit, B
Abstract: The emergency situations generated by the earthquakes in Chile have revealed the country's lack of preparation to face these kinds of disasters. Many educational buildings were destroyed by these natural events. In response, a system of modular schools was implemented. Although these have been a temporary fast solution, they have not met the needs that a classroom demands. This article focuses on studying daylighting strategies to achieve the visual comfort of students, as many investigations indicate that this is one of the key environmental factors in their wellbeing and performance. The article also focuses on achieving a correct distribution of horizontal illuminance by implementing design strategies, looking to achieve uniformity inside classrooms, avoiding annoying glare points. The implementation of these strategies fosters the use of daylight in order to reduce the energy consumption of artificial lights and generate optimal conditions for students to perform their school activities. The studied classroom is a modular prototype located in Temuco, Chile, and the evaluated strategies were defined based on the "Guía de Eficiencia Energética para Establecimientos Educacionales (Energy Efficiency Guide for Educational Facilities or GEEEduc)". These were evaluated independently in order to compare, starting from the results obtained from computer simulations, the compliance of the lighting comfort standards set out in said guide, focusing on the light uniformity and illuminance level indicators. The strategies with the best results were later evaluated in detail, ultimately reaching the case with the best performance. The study proved there are several ways to respond to the presented need, allowing concluding from a set of evaluated strategies, which one of them better serves the required standards. Likewise, implementing strategies of the "GEEEduc" as well as its indicators, results in a practical application of this guideline, allowing the identification of potential errors and good options for future applications.